2021
DOI: 10.18203/issn.2454-2156.intjscirep20213261
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the uptake of community-based health insurance in Ethiopia: a systematic review

Abstract: <p class="abstract">The goal of health care financing in Ethiopia is achieving universal health care coverage by community-based health insurance which was expected to cover more than eighty percent of the population. The aim was to minimize catastrophic out-of-pocket health service expenditure. We systematically reviewed factors affecting the uptake of community-based health insurance in Ethiopia. We searched various databases by 09 to 10 March 2019. We included articles regardless of their publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
4
10
1
Order By: Relevance
“…This study was in line with the previous study [ 18 , 26 , 27 ], which indicates the age of household age significantly positively affected CBHI enrollment. This study contradicted the previous study [ 28 ], age is not a significant predictor of CBHI scheme enrollment. This may be due to the fact that older people are more afraid of impending illness than younger people.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study was in line with the previous study [ 18 , 26 , 27 ], which indicates the age of household age significantly positively affected CBHI enrollment. This study contradicted the previous study [ 28 ], age is not a significant predictor of CBHI scheme enrollment. This may be due to the fact that older people are more afraid of impending illness than younger people.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with those from other settings elsewhere [ 29 31 ], which shows the richest households were more likely to use the CBHI program when compared the poorest households. In addition, it is in line with the previous studies [ 26 , 28 , 32 , 33 ], which show income significantly positively affected CBHI enrollment. This study was not in line with the previous studies [ 34 ], poor wealth status households were more likely willing to pay/enroll for CBHI than rich household heads.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To do so, many developing countries have introduced CBHI since the 1990s to strengthen healthcare financing and improve access to healthcare by reducing costly risk-coping strategies ( 28 ). However, its uptake has been challenged by a variety of factors, including satisfaction ( 29 ), demographic, socio-economic, health status, and health services issues ( 30 ). Moreover, treatment outcome and patient satisfaction are inseparable ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, to ensure equitability, the premiums should be based on income levels ( 37 ). On the other hand, as livestock size increased with income, the farmers’ interest in implementing the scheme decreased because the livestock were considered to be reserved assets ( 30 ). Despite the far distance, this study showed that rural respondents were more satisfied than urban dwellers, which did not deter households from joining the scheme ( 12 ); i.e., the rural and informal sectors, in particular, benefited from this program ( 32 ).…”
Section: Discussionmentioning
confidence: 99%